Expression changes of ER, PR, HER2, and Ki-67 in primary and metastatic breast cancer and its clinical significance - Hu, Xueyang; Chen, Wenjun; Li, Fanfan; Ren, Pengfei; Wu, Hongyang; Zhang, Congjun; Gu, Kangsheng (Frontiers in Oncology, 2023)
Objective: To explore the altered expression of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), and cell proliferation index (Ki-67) in primary and metastatic breast cancer lesions and the correlation between the primary tumor size, lymph node metastasis, Tumor Node Metastasis (TNM) stage, molecular typing, and disease-free survival (DFS) and their clinical significance. Methods: A retrospective analysis was conducted on the clinical data of 130 patients with metastatic breast cancer biopsy admitted to the Cancer Center of the Second Affiliated Hospital of Anhui Medical University in Hefei, China, from 2014–2019. The altered expression of ER, PR, HER2, and Ki-67 in primary and metastatic lesions of breast cancer was analyzed with respect to the site of metastasis, size of the primary tumor, lymph node metastasis, disease progression, and prognosis. Results: The inconsistent expression rates of ER, PR, HER2, and Ki-67 in primary and metastatic lesions were 47.69%, 51.54%, 28.10%, and 29.23%, respectively. The size of the primary lesion was not, but that accompanied by lymph node metastasis was related to the altered receptor expression. Patients with positive ER and PR expression in both primary and metastatic lesions had the longest DFS, while those with negative expression had the shortest DFS. Also, changes in HER2 expression in primary and metastatic lesions were not associated with DFS. Patients with low expression of Ki-67 in both primary and metastatic lesions had the longest DFS, while patients with high expression had the shortest DFS. Conclusion: Heterogeneity was detected in the expression levels of ER, PR, HER2, and Ki-67 in the primary and metastatic breast cancer lesions, which has a guiding significance for the treatment and prognosis of patients.